2015
DOI: 10.1108/ijpsm-04-2015-0073
|View full text |Cite
|
Sign up to set email alerts
|

Learning to co-produce? The perspective of public service professionals

Abstract: Purpose – The purpose of this paper is to report on how public service professionals cope with co-production as a way to produce and develop public services. Design/methodology/approach – The paper draws on the literature of co-production and collaborative public service innovation. The research approach was an explorative case study, presenting a pilot neighbourhood co-production project. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 36 publications
0
78
0
8
Order By: Relevance
“…When professionals perceive more autonomy in co-production, this increases the likelihood they are engaged in co-production (Van Eijk et al 2017a). Furthermore, studies show that organizational culture can be either stimulating or hindering for professionals to feel engaged (Van Eijk et al 2017a;Tuurnas 2015). Organizational culture manifests itself in institutions, social relations and habits, and originates largely in management or leadership (Normann 2007: 214-215).…”
Section: Being Engaged In Co-productionmentioning
confidence: 99%
See 2 more Smart Citations
“…When professionals perceive more autonomy in co-production, this increases the likelihood they are engaged in co-production (Van Eijk et al 2017a). Furthermore, studies show that organizational culture can be either stimulating or hindering for professionals to feel engaged (Van Eijk et al 2017a;Tuurnas 2015). Organizational culture manifests itself in institutions, social relations and habits, and originates largely in management or leadership (Normann 2007: 214-215).…”
Section: Being Engaged In Co-productionmentioning
confidence: 99%
“…Earlier studies show that not all citizens and professionals are engaged in co-production equally or for similar reasons (Van Eijk and Steen 2014;Tuurnas 2015). Professionals, for example, differ in the extent to which they are convinced of the importance and impact of co-production, and the extent to which they feel personally involved (Van Eijk et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Steen (2014, 2016) conducted empirical research in Belgium and the Netherlands into the motivations of citizens to co-produce, and concluded that these motivations are based on a combination of three factors -community oriented drivers, self-interest, and finally a perception of the difficulty of co-production and the extent of their ability to contribute. On the side of the 'regular service providers', Tuurnas (2015) studied why professionals take part in co-production and how they manage the introduction of co-production pilot projects. In the case study she examined in Finland, she found that a dramatic change in culture was needed from the side of professionals, an argument which has been made previously (Bovaird, 2007).…”
Section: Empirical Evidence Of Co-productionmentioning
confidence: 99%
“…2) Participative co-production (Tuurnas, 2015), which goes beyond the operational level and concerns simultaneously co-planning, co-design and co-delivery of existing services;…”
Section: Theoretical Frameworkmentioning
confidence: 99%